Caracterización de los estilos de crianza en familias de niños y niñas con comportamientos disruptivos de una Institución Educativa de Riohacha. (2023)
Parenting styles are strategies used by parents to guide the process of training each child. The main objective of the research was to describe the parenting styles of the families of boys and girls who present disruptive behaviors in the fifth grade of the Happy Kids Stimulation and Teaching Center of the Special, Tourist and Cultural District of Riohacha, to achieve the purposes of the study. The study was carried out under a quantitative approach, a descriptive method and the participants were 49 students and their parents. This population belongs to the Happy Kids Stimulation and Teaching Center. The PSDQ questionnaire for parents and the observation grid were applied to record aggressive behavior in students. Regarding the results, it was found that there is a predominance in the implementation of the authoritative parenting style, followed by authoritarian and permissive; Regarding aggressive behaviors, it is evident that there is a similarity in the types of physical and verbal aggressive behaviors of the fifth grade.